Understanding the Relationship Between Grit and Foreign Language Performance Among Middle School Students: The Roles of Foreign Language Enjoyment and Classroom Environment - Wei, Hongjun; Gao, Kaixuan; Wang, Wenchao (Frontiers in Psychology, 2019)
Objective: This study aims to examine the effect of grit on foreign language performance (FLP) among middle school students. A mediated moderation model was constructed to assess the mediating role of foreign language enjoyment (FLE) and the moderating role of classroom environment (CE) in the relationship between grit and FLP. Method: The study adopted the Grit Scale-Short Version, the Chinese Version of the FLE Scale, and the English CE Inventory to investigate 832 middle school students, and recorded the students' FLP of final exam after one month. Correlation and regression analyses were used to evaluate the relationships between grit, FLE, CE, and FLP. Results: The results indicated that grit positively affected FLP. In addition, FLE mediated the relationship between grit and FLP, and CE moderated the relationship between grit and FLE, and between grit and FLP. Conclusions: Grit not only directly promotes the FLP of middle school students but also indirectly improves FLP by promoting FLE. In addition, the impact of grit on FLE and FLP increases in a positive CE.